Resolution of Land Disputes Between the Government and the Community Related to Overlapping Land Rights - Cahyani Putri, Amanda Dwi; Kamal, Ubaidillah (IHSA Institute, 2025)
Land disputes between the government and the community, especially related to overlapping land rights, have become an important issue in land governance. This research aims to identify the causes of disputes and the forms of their resolution. The method used is a qualitative approach with an empirical legal research type through field studies at the Land Office and the City Spatial Planning Department in Semarang. Data were obtained through interviews and documentation, and then analyzed qualitatively in a descriptive manner. The results indicate that the main causes of disputes include inaccuracies in tracing land history, measurements conducted without involving legitimate owners, the absence of a legal basis for issuing usage rights, and PTSL procedures that do not comply with regulations. Resolutions are carried out through non-litigation pathways such as mediation and conciliation, as well as litigation avenues through the Administrative Court (PTUN). As a result of this case, the PTUN stated that it does not have jurisdiction to examine the matter because the core of the dispute concerns land ownership, which falls under the jurisdiction of general courts. This research emphasizes the importance of accurate validation of land data to prevent disputes in the future